2004
DOI: 10.1073/pnas.0305400101
|View full text |Cite
|
Sign up to set email alerts
|

Ly49Q, a member of the Ly49 family that is selectively expressed on myeloid lineage cells and involved in regulation of cytoskeletal architecture

Abstract: Here, we identified and characterized a Ly49 family member, designated as Ly49Q. The Ly49q gene encodes a 273-aa protein with an immunoreceptor tyrosine-based inhibitory motif (ITIM) at the N terminus of its cytoplasmic domain. We show that the ITIM of Ly49Q can recruit SHP-2 and SHP-1 in a tyrosine phosphorylation-dependent manner. In contrast to other known members of the Ly49 family, Ly49Q was found not to be expressed on NK1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
80
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 42 publications
3
80
1
Order By: Relevance
“…The finding that Ly49B was expressed on myeloid cells suggested that its pattern of expression might be similar to that of Ly49Q, which was recently reported to be expressed at high levels on DC and at lower levels on some other myeloid populations (13,16,32). However, as shown in Fig.…”
Section: Comparative Expression Of Ly49b and Ly49qcontrasting
confidence: 40%
“…The finding that Ly49B was expressed on myeloid cells suggested that its pattern of expression might be similar to that of Ly49Q, which was recently reported to be expressed at high levels on DC and at lower levels on some other myeloid populations (13,16,32). However, as shown in Fig.…”
Section: Comparative Expression Of Ly49b and Ly49qcontrasting
confidence: 40%
“…Ly49Q is expressed on myeloid lineage cells, in particular plasmacytoid dendritic cells (4,31). Thus, cell types other than NK cells use receptor masking to adapt receptor accessibility and consequently receptor function to self-MHC-I.…”
Section: Ly49b and Ly49qmentioning
confidence: 99%
“…In C57BL/6 (B6) mice, 14 Ly49 genes have been identified, four of which are pseudogenes (2). Whereas the majority of the Ly49 receptors are expressed by NK cells, Ly49B and Ly49Q, which are located at either end of the Ly49 gene complex, are not expressed by NK cells (3,4). Rather, Ly49Q is found on myeloid lineage cells (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, two Ly49, Ly49B and Ly49Q, are expressed on myeloid-derived cells, including macrophages, neutrophils, and DCs (6,7). Initial cDNA screening of inbred mouse strains revealed extreme genetic diversity and polymorphism in different mouse strains (8), which was later revealed to be a result of genomic plasticity within the Ly49 region resulting in cluster sizes ranging from 8 to 22 Ly49 genes (9,10).…”
mentioning
confidence: 99%